2017
DOI: 10.1002/brb3.719
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cognitive impairment and motor dysfunction in Parkinson's disease

Abstract: IntroductionNumerous studies have been carried out to explore the potential association between neurologic deficits and variable clinical manifestations of Parkinson's disease (PD). The aim of our study was to investigate the association between cognitive performance and motor dysfunction in Chinese patients with PD.MethodsData from 96 patients with PD were obtained from the Parkinson's disease patient cohort database of Huashan Hospital. All participants underwent a comprehensive neuropsychological evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Prevalence was significantly moderated by disease stage evaluated by H&Y only, suggesting that PD‐MCI often develops during the disease course when the neurodegenerative process affects several cortical and subcortical areas, as highlighted in previous studies . This relationship is also supported by the findings of a significant difference between patients with and without PD‐MCI on the severity of motor symptoms, LEDD, and disease duration.…”
Section: Discussionsupporting
confidence: 77%
“…Prevalence was significantly moderated by disease stage evaluated by H&Y only, suggesting that PD‐MCI often develops during the disease course when the neurodegenerative process affects several cortical and subcortical areas, as highlighted in previous studies . This relationship is also supported by the findings of a significant difference between patients with and without PD‐MCI on the severity of motor symptoms, LEDD, and disease duration.…”
Section: Discussionsupporting
confidence: 77%
“…In our previous study, we reported a significant correlation between subdomains of cognitive impairment and motor dysfunction, suggesting shared neurochemical pathways (Wang et al, 2017). In a previous study, PD-D patients exhibit greater dopamine depletion than nondemented patients (Emre, 2003).…”
Section: Cognitive Profile In Pd Patients and Healthy Controlsmentioning
confidence: 84%
“…These findings are consistent with past observations showing that motor dysfunction is associated with cognitive decline, autonomic dysfunction, and RBD. 28,48 PD with RBD is also associated with faster motor progression and a higher risk of cognitive decline. 28 In line with these studies, we found that patients with biotype 1 had much worse RBD symptomatology and more cognitive decline.…”
Section: Discussionmentioning
confidence: 99%